Students' Perceptions on Vlog as Speaking Assessment Technique at Senior High School - Karlina Sharon J.H; Nurlaily Nurlaily (Institut Agama Islam Negeri Palopo, 2022)
Vlogs among students are highly viral and beneficial for developing their language skills as a learning technique. In this study, the researcher were interested in describing how to assess students' speaking performance through fluency and pronunciation using Vlogs and how students perceived it as an assessment. The subjects of the study were students from grade tenth science three from Yos Sudarso School. Since the phenomena of pandemic is happening, hence a backup plan is required for study specifically at home. This research aims to explain how students’ speaking performance also finding out students’ first impression on the use of Vlog as a speaking assessment at SMA Yos Sudarso. The method to collect the data of this research is sequential design which is both qualitative and quantitative. This first phase was accompanied by the compilation and analysis of qualitative data in order to discuss or build on the first phase of quantitative results. The subsequent qualitative phase of the analysis was structured to be focused on the outcomes of the quantitative phase. The data of the students' speaking performance through Vlog show that most of the students have a good result in speaking through Vlog but some of the students are having difficult experience to speak in front of the camera. The research results are expected to be useful and give relevant data on how students of English, as a foreign language, use vlog as learning tool to assess speaking English performance and provide teachers innovations in utilizing the latest digital technology and trends in their teaching. As an evaluation, it is also expected that the result of this study can be meaningful feedback for the study program and the lecturer of the Speaking course.